Crossroads of freedom slaves and freed people in Bahia, Brazil, 1870-1910 - Fraga Filho, Walter 1963- (Duke University Press, 2016)
Slaves and masters on sugar plantations in the last decades of slavery -- Tension and conflict on a Recôncavo sugar plantation -- Crossroads of slavery and freedom, 1880-1888 -- May 13, 1888, and its immediate aftermath -- Heads spinning with freedom -- After abolition: tension and conflict on Recôncavo sugar plantations -- Trajectories of slaves and freed people on Recôncavo sugar plantations -- Community and family life among freed people -- Other post-emancipation itineraries -- In the centuries to come: projections of slavery and freedom